Preparation method and application of anti-static aluminum oxide ceramic

CN121470930BActive Publication Date: 2026-10-09HANGZHOU DAHE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511303976.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2026-10-09
Estimated Expiration
2045-09-12

AI Technical Summary

Technical Problem

[0007]为解决生产工艺繁琐的问题,同时扩大防静电陶瓷的使用温度范围,本发明提出一种防静电氧化铝陶瓷及其制备方法与应用,制备工艺简单,适用于大规模的工业化生产,制备得到的防静电氧化铝陶瓷致密度良好,不仅体积电阻率符合国标要求,而且高温下体积电阻率较稳定,适用于半导体设备用陶瓷搬运手臂

Benefits of technology

[0027] This invention employs a doped composite conductive filler method and an aqueous granulation system, resulting in lower costs and safer operation. The obtained antistatic alumina ceramic can achieve a volume resistivity of 1 x 10⁻⁶ at room temperature. 7 Ω·cm, meeting the national standard requirements for this type of material, with stable volume resistivity at high temperatures; suitable for wafer handling arms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121470930B_ABST
    Figure CN121470930B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of alumina ceramics, and aims to solve the problem of complicated production process and expand the use temperature range of the anti-static ceramic, and provides a preparation method and application of anti-static alumina ceramic: firstly, alumina micro powder, silicon carbide micro powder, titanium carbide micro powder and yttrium oxide micro powder are mixed with water and then a dispersing agent is added, ball milling is carried out to form slurry 1; secondly, the slurry 1 is mixed with a binder and then sand milling is carried out, and sieving is carried out to obtain slurry 2; then, the slurry 2 is made into granulation powder; finally, the granulation powder is formed into a green body, the green body is degreased, argon powder burying sintering is carried out, and the anti-static ceramic material is obtained. The preparation process is simple, is suitable for large-scale industrial production, the prepared anti-static alumina ceramic has good compactness, the volume resistivity meets the national standard requirements, the volume resistivity is relatively stable at high temperature, and the anti-static alumina ceramic is suitable for ceramic handling arms for semiconductor equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alumina ceramics technology, and in particular to a method for preparing and applying antistatic alumina ceramics. Background Technology

[0002] Antistatic materials generally refer to materials that can safely release static charges. They can be divided into antistatic coatings, polymer composites, and antistatic ceramic materials. While antistatic coatings possess good antistatic properties, their lack of wear resistance limits their widespread use in high-end semiconductor equipment. Antistatic polymer composites typically consist of a conductive network and a resin substrate; however, their antistatic properties are relatively weak, failing to meet the expectations of the target market. Compared to other types of materials, antistatic ceramics are not only wear-resistant and corrosion-resistant with high safety performance, but also possess advantages such as fire and water resistance and chemical stability. Ceramic materials themselves are non-conductive; for example, alumina, with high-purity alumina typically exhibiting a volume resistivity of 1×10⁻⁶. 15 ~9×10 16 Ω·cm, therefore, antistatic ceramics usually need to be doped with conductive fillers to form conductive paths, such as antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), zinc oxide, silicon carbide and other materials.

[0003] According to the national standard GB 50611-2010, electrostatic dissipative antistatic ceramics generally refer to those with a surface resistivity or volume resistivity of 1×10⁻⁶. 6 ~1×10 9 Materials within the Ω range. Static charges can move on static dissipative materials, but they need to overcome a certain resistance. Because of this characteristic, static electricity will be slowly released when passing through such materials, without a short period of high current, which can prevent static electricity from damaging the product.

[0004] It meets the national standard requirements for this type of material and has a more stable volume resistivity at high temperatures; it is suitable for wafer handling arms.

[0005] Patent CN113698182B discloses an antistatic alumina ceramic material and its preparation method. The disclosed alumina / silicon carbide composite antistatic ceramic material uses a gel casting method, which has high operational requirements and cannot be mass-produced using machines. Patent CN115353381B discloses large-size zirconia antistatic ceramics, their preparation method, and applications. The zirconia material used in this patent is conductive at high temperatures, which greatly affects its antistatic performance. Although adding a small amount of titanium carbide can solve this problem and reduce the volume resistivity at room temperature, titanium carbide is a material with very high sintering requirements. At high addition levels, a hot-pressing sintering process is required, and sintering still needs to be carried out at a high temperature of 2100℃. Furthermore, adding a high content of silicon carbide to alumina leads to a decrease in the density of the ceramic itself.

[0006] Therefore, in order to overcome the above problems, expand the operating temperature range of antistatic ceramics, and solve the problem of cumbersome production processes, it is crucial to develop an antistatic ceramic and its production method that are more suitable for industrial production. This will play an important role in the application of antistatic ceramics in high-end semiconductor equipment. Summary of the Invention

[0007] To address the issue of cumbersome production processes and expand the operating temperature range of antistatic ceramics, this invention proposes an antistatic alumina ceramic, its preparation method, and its application. The preparation process is simple and suitable for large-scale industrial production. The prepared antistatic alumina ceramic exhibits good density, with its volume resistivity meeting national standards and remaining relatively stable at high temperatures, making it suitable for ceramic handling arms used in semiconductor equipment.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing an antistatic alumina ceramic material includes the following steps: (1) Slurry ball milling: Alumina micro powder, silicon carbide micro powder, titanium carbide micro powder, yttrium oxide micro powder are mixed with water and then a dispersant is added. The mixture is then ball milled to form slurry 1. Preferably, the weight parts of the alumina micro powder, silicon carbide micro powder, titanium carbide micro powder, and yttrium oxide micro powder are 69-77:15-25:1-5:0.5-3, respectively.

[0009] Preferably, the alumina micro powder has a particle size of D. 10 : 0.2-0.4µm, D 50 : 0.5-0.7µm, D 90 : 2-4µm; alumina micro powder has fine particle size and high activity, which is beneficial for sintering.

[0010] Preferably, the silicon carbide micro powder has a particle size of D. 10 : 0.1-0.3µm, D 50 : 0.4-0.6µm, D 90 : 0.9-1.1µm; used as a conductive filler for antistatic ceramics.

[0011] Preferably, the titanium carbide micro powder has a particle size of D. 10 : 0.1-0.2µm, D 50 : 0.3-0.4µm, D 90 : 0.5-0.6µm; used as a conductive filler for antistatic ceramics, and the antistatic ceramics exhibit strong volume resistivity stability at high temperatures after the addition of titanium carbide.

[0012] Preferably, the yttrium oxide micro powder has a particle size of D. 10: 0.3-0.5µm, D 50 : 0.8-1.0µm, D 90 : 1.4-1.6µm; used as a sintering aid.

[0013] The dispersant is a mixture comprising an alumina dispersant and a silicon carbide dispersant. Preferably, the amount of alumina dispersant used is 0.4%-0.8% of the weight of the alumina micro powder; the amount of silicon carbide dispersant used is 0.4%-0.8% of the weight of the silicon carbide micro powder.

[0014] The alumina dispersant is selected from ammonium salt type carboxylic acid copolymers, and the silicon carbide dispersant is selected from polyacrylate-based composite dispersants.

[0015] Preferably, the slurry 1 has a solid content of 65%-70% and a viscosity of less than 100 Pa·s, which is beneficial for spray granulation.

[0016] Preferably, the ball milling time is determined by the weight of the powder, which is (2-3) kg / hour.

[0017] (2) Slurry grinding: Slurry 1 is mixed with binder and then ground and sieved to obtain slurry 2.

[0018] Preferably, the binder is selected from polyvinyl alcohol-based composite binders, and the amount of binder used is 5-7% of the weight of the micro powder. The micro powder is alumina micro powder, silicon carbide micro powder, titanium carbide micro powder, or yttrium oxide micro powder.

[0019] As a preferred method, the slurry after sand milling is sieved using a clean 300-400 mesh screen.

[0020] Preferably, the ball milling time is determined by the weight of the powder, (1-2) Kg / hour.

[0021] (3) Spray drying: The slurry 2 is made into granulated powder.

[0022] As a preferred method, a granulation tower is used for spray granulation, with an inlet temperature of 160-200 ℃ and an outlet temperature of 60-80 ℃.

[0023] (4) The granulated powder is shaped into a green body, and the green body is degreased, argon-embedded powder is sintered to obtain an antistatic ceramic material.

[0024] Preferably, the granulated powder is formed into a green body by dry pressing or cold isostatic pressing.

[0025] The degreasing process is as follows: the temperature is increased to 600-800℃ in nitrogen at a rate of 15-25℃ / h, and held for 1-2 hours.

[0026] The sintering process is as follows: the temperature is raised to 1000-1100℃ in a vacuum atmosphere at a rate of 50-100℃ / h, and then raised to 1900-2000℃ in an argon atmosphere at a rate of 15-25℃ / h, and held for 3-7h.

[0027] This invention employs a doped composite conductive filler method and an aqueous granulation system, resulting in lower costs and safer operation. The obtained antistatic alumina ceramic can achieve a volume resistivity of 1 x 10⁻⁶ at room temperature. 7 Ω·cm, meeting the national standard requirements for this type of material, with stable volume resistivity at high temperatures; suitable for wafer handling arms.

[0028] Compared with the prior art, the beneficial effects of the present invention are: the preparation process of the present invention is simple and suitable for large-scale industrial production. The prepared antistatic alumina ceramic has good density, and not only does its volume resistivity meet the requirements, but its volume resistivity is also stable at high temperatures. Attached Figure Description

[0029] Figure 1 This is an SEM image of the antistatic ceramic prepared in Example 3. Detailed Implementation

[0030] The specific embodiments of the present invention will be further described below.

[0031] Unless otherwise specified, all raw materials used in this invention are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following examples are conventional methods in the art. Unless otherwise specified, all parts are parts by weight (one part is 1 gram), temperatures are expressed in °C or at ambient temperature, and pressures are at or near atmospheric pressure. Various variations and combinations of reaction conditions (e.g., component concentrations, required solvents, solvent mixtures, temperature, pressure, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method exist, and only reasonable routine experiments are needed to optimize such method conditions.

[0032] The alumina powder used in the examples has a particle size of D. 10 : 0.3µm, D 50 0.5µm, D 90 3µm; the fine particle size and high activity of alumina micro powder are conducive to sintering.

[0033] The particle size of the silicon carbide micro powder used in the examples is D. 10 : 0.2µm, D 50 0.5µm, D 90 1µm; used as a conductive filler for antistatic ceramics.

[0034] The titanium carbide micropowder used in the examples has a particle size of D.10 : 0.2µm, D 50 : 0.3µm, D 90 : 0.5µm; used as a conductive filler for antistatic ceramics, and the antistatic ceramics exhibit strong volume resistivity stability at high temperatures after the addition of titanium carbide.

[0035] The particle size D of the yttrium oxide micro powder used in the examples 10 : 0.4µm, D 50 0.9µm, D 90 1.5µm; used as a sintering aid.

[0036] Example 1 A method for preparing antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3450 parts alumina, 1250 parts silicon carbide, 250 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 20.7 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 7.5 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0037] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0038] (3) Spray drying: The slurry 2 obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0039] (4) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1900℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0040] Example 2 A method for preparing antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 4150 parts alumina, 750 parts silicon carbide, 50 parts titanium carbide powder, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 24.9 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 4.5 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0041] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0042] (3) Spray drying: The slurry obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0043] (3) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 2000℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0044] Example 3 A method for preparing antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3700 parts alumina, 1100 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 22.2 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 6.6 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0045] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0046] (3) Spray drying: The slurry 2 obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0047] (4) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1900℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0048] Comparative Example 1 The difference from Example 3 is that the sintering temperature is lower than the preferred range. A method for preparing an antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3700 parts alumina, 1100 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 22.2 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 6.6 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0049] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0050] (3) Spray drying: The slurry 2 obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0051] (4) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1800℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0052] Comparative Example 2 The difference from Example 3 is that the silicon carbide content in step (1) is lower than the preferred range. A method for preparing an antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 4450 parts alumina, 350 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 26.7 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 2.1 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain a slurry with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0053] (2) Slurry grinding: Pour the slurry obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pass the slurry through a 325-mesh clean sieve and pour it into a collection device.

[0054] (3) Spray drying: The slurry obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0055] (4) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1900℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0056] Comparative Example 3 The difference from Example 3 is that the silicon carbide content in step (1) is higher than the preferred range. A method for preparing an antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3450 parts alumina, 1350 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 20.7 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 8.1 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0057] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0058] (3) Spray drying: The slurry obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0059] (4) Powder forming: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150 x 150 x 45 mm and a dry pressing pressure of 20 MPa; then, cold isostatic pressing is performed with a forming pressure of 120 MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1900℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0060] Comparative Example 4 The difference from Example 3 is that the heating rate in step (5) of the sintering process is higher than the preferred range. A method for preparing antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3700 parts alumina, 1100 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 22.2 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 6.6 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0061] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0062] (3) Spray drying: The slurry 2 obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0063] (4) Powder molding: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150X150X45 mm and a dry pressing pressure of 20MPa; then, cold isostatic pressing is performed with a molding pressure of 120MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 50℃ / h, and held at 600℃ for 2 hours. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 120℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 50℃ / h, and held at 1900℃ for 5 hours. Subsequently, it was naturally cooled to room temperature to obtain antistatic alumina ceramic material. The material had external cracks and obvious color differences inside, and the result was unqualified.

[0064] Comparative Example 5 The difference from Example 3 is that a different dispersant was used in step (1): (1) Slurry ball milling: In a ball milling jar, add 3700 parts alumina, 1100 parts silicon carbide, 150 parts titanium carbide, 50 parts yttrium oxide powder, 10000 parts zirconium oxide grinding beads, 2692 parts pure water, 22.2 parts citric acid as alumina dispersant, and 6.6 parts tetramethylammonium hydroxide as silicon carbide dispersant. Ball mill for 2 hours to obtain a slurry with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0065] (2) Slurry grinding: Pour the slurry obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pass the slurry through a 325-mesh clean sieve and pour it into a collection device.

[0066] (3) Spray drying: The slurry obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0067] (4) Powder molding: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150X150X45 mm and a dry pressing pressure of 20MPa; then, cold isostatic pressing is performed with a molding pressure of 120MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1900℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0068] Because unsuitable dispersants were used, citric acid was used as an alumina dispersant at a pH of around 3, while tetramethylammonium hydroxide was used as a silicon carbide dispersant at a pH of around 10. The absolute value of the Zeta potential of alumina was relatively high at both pH 3 and 10, indicating good dispersibility in solution at these pH values. In contrast, the absolute value of the Zeta potential of silicon carbide was only relatively high at pH 10, indicating good dispersibility. When citric acid and tetramethylammonium hydroxide were mixed, the pH gradually tended towards neutral to acidic, significantly reducing the dispersibility of both alumina and silicon carbide. This led to powder agglomeration during ball milling, ultimately resulting in uneven silicon carbide dispersion. The volume resistivity tested in this example fluctuated greatly, with a measurable range of 9.8 x 10⁻⁶. 6 ~3.8X10 8 Ω·cm.

[0069] Comparative Example 6 A method for preparing antistatic alumina ceramic is as follows: (1) Slurry ball milling: In a ball milling jar, add 3650 parts alumina, 1250 parts silicon carbide, 50 parts yttrium oxide powder, 10000 parts zirconia grinding beads, 2692 parts pure water, 21.9 parts ammonium salt type carboxylic acid copolymer as alumina dispersant, and 7.5 parts polyacrylate-based composite dispersant. Ball mill for 2 hours to obtain slurry 1 with a solid content of 65% and a viscosity of less than 100 Pa·s.

[0070] (2) Slurry grinding: Pour the slurry 1 obtained in step (1) into a sand mill, add 543 parts of polyvinyl alcohol composite binder with a solid content of 46% and 10,000 parts of zirconium oxide grinding beads with a diameter of 5mm. After grinding for 5 hours, pour the slurry 2 through a 325-mesh clean sieve into a collection device.

[0071] (3) Spray drying: The slurry 2 obtained in step (2) is slowly pumped into the spray drying tower through the feed pump. The inlet temperature is set to 180°C and the outlet temperature is set to 75°C for spray granulation. The granulated powder is then screened to obtain granulated powder.

[0072] (4) Powder molding: First, the granulated powder obtained in step (3) is dry-pressed into blocks with a size of 150X150X45 mm and a dry pressing pressure of 20MPa; then, cold isostatic pressing is performed with a molding pressure of 120MPa to obtain a green body. The obtained green body was placed in a nitrogen-protected degreasing furnace for degreasing, with a heating rate of 15℃ / h, and held at 600℃ for 2h. In the early stage of the sintering process, powder sintering was carried out under vacuum atmosphere with a heating rate of 50℃ / h. When the temperature reached 1000℃, the powder sintering was switched to argon atmosphere with a heating rate of 15℃ / h, and held at 1800℃ for 5h. Then, the temperature was naturally cooled to room temperature to obtain antistatic alumina ceramic material.

[0073] Comparative Example 7 An antistatic ceramic semiconductor handling arm manufactured by a commercially available company was processed and its performance was tested, and then compared with the product developed in this patent.

[0074] Performance testing Antistatic performance analysis Table 1. Room temperature volume resistivity results of materials from different embodiments and comparative examples

[0075] Examples 1-3, and Comparative Examples 1-3, and Comparative Example 7 mainly investigated the effect of conductive fillers on volume resistivity at room temperature. Table 1 lists the room temperature density and volume resistivity of the sintered bodies. The testing standards were based on GB / T 31838.2-2019 Solid insulating materials, dielectric and resistive properties, Part 2: Resistive properties (DC method), Volume resistivity and volume resistivity testing standards.

[0076] All the volume resistivity tests mentioned above were conducted using the three-ring electrode method. The samples were all processed into small pieces of 25*25*1mm, and the upper and lower surfaces were coated with silver paste before testing.

[0077] The results obtained from the above three embodiments all meet the requirements of the national standard for antistatic ceramics. Pure titanium carbide typically requires a temperature above 2000℃ to be fully sintered and densified under pressureless sintering. When it is used as an additive and sintered simultaneously with alumina, the sintering temperature of titanium carbide is higher than that of alumina because the melting point of titanium carbide (3140℃) is higher than that of alumina (2050℃). Therefore, the addition of titanium carbide will hinder the sintering of antistatic ceramics.

[0078] Comparative Example 6, without the addition of titanium carbide, could be successfully sintered at 1800℃. However, in Comparative Example 1, the antistatic ceramic with added titanium carbide exhibited a decrease in density. During sample preparation, numerous defects were visible to the naked eye when the material was cut open, and powder shedding occurred on the material surface. In Example 3, after increasing the sintering temperature by 100℃, the antistatic ceramic with added titanium carbide was successfully sintered, and the test block formed a ceramic without powder shedding.

[0079] Adding conductive fillers to impart conductivity to a material is a complex process. The conductivity process can be broadly categorized into two types: one is through the chain structure of conductive particles providing channels for charge carrier transfer, and the other is through the tunneling effect formed between the conductive filler particles and the polymer. Therefore, most antistatic ceramic materials have a slightly lower density than conventional (above 99%) dense ceramics, such as Examples 1, 2, and 3, whose relative densities are only around 95%. However, a small number of defects within the material can promote an increase in resistivity, as in Example 3. Conversely, a large number of defects will hinder the formation of conductive pathways, as in Comparative Example 1. When silicon carbide is added in excess or insufficient amounts, the volume resistivity of the antistatic ceramic also changes accordingly. When the addition amount is outside the recommended range, the silicon carbide content in Comparative Example 2 is less than the preferred range, and its volume resistivity increases to 10. 11 In Comparative Example 3, the silicon carbide content was greater than the preferred range, and its volume resistivity decreased to 10 Ω·cm. At 1900℃, alumina exhibited overheating, with noticeable abnormal grain growth, resulting in a relatively loose material density of only 97%. 5 If the final volume resistivity is too low (Ω·cm), excessive current during use can cause breakdown and damage to the semiconductor components it carries.

[0080] Compared to Comparative Example 7, Examples 2 and 3 have slightly higher volume resistivity, but still remain within the range of the national standard for antistatic ceramics. This is because the formulations in this series balance density and volume resistivity to achieve higher density. Furthermore, for Example 3, this volume resistivity effectively prevents the performance failure of the antistatic ceramic at high temperatures. Compared to Comparative Example 7, Example 1 has a lower volume resistivity, but still remains within the range recommended by the national standard. Figure 1 The image shown is an SEM image of the antistatic ceramic prepared in Example 3. It can be clearly observed that a large number of silicon carbide grains grow between the alumina grain boundaries, forming a conductive path.

[0081] Examples 3, 1, 6, and 7 mainly investigated the effects of titanium carbide addition and sintering temperature on volume resistivity at room temperature. Table 2 lists the volume resistivity of the sintered bodies. The testing standard was based on GB / T 31838.2-2019 Solid insulating materials, dielectric and resistive properties, Part 2: Resistive properties (DC method) – Volume resistivity and volume resistivity testing standards.

[0082] Table 2. Volume resistivity results of materials at different sintering temperatures

[0083] All the volume resistivity tests mentioned above were conducted using the three-ring electrode method. The samples were all processed into small pieces of 25*25*1mm, and the upper and lower surfaces were coated with silver paste before testing.

[0084] Compared with Example 3, Comparative Example 6 removed titanium carbide and used a lower sintering temperature, while Comparative Example 1 only reduced the sintering temperature. Comparing Example 3 and Comparative Example 6, it can be found that removing titanium carbide makes the material easier to sinter overall, and both the material's density and resistivity are improved. However, correspondingly, because no titanium carbide was added, the resistivity of the material prepared in Comparative Example 6 lost its antistatic effect at 500°C. Comparative Example 1 reduced the sintering temperature, and although the volume resistivity of the material met the national standard requirements and was relatively stable at high temperatures, its lower density and numerous defects prevented it from being used as a qualified product. Comparative Example 7 is a commercially available imported antistatic ceramic handling arm. Comparing it with Example 3 and Comparative Example 6, it can be found that the qualified product of this patent has a higher density, and without the addition of titanium carbide, its volume resistivity is better than that of the commercially available product. With the addition of titanium carbide, the stability of its volume resistivity is also better than that of the commercially available product.

[0085] Examples 1, 2, 3 and Comparative Example 7 were studied for volume resistivity at high temperatures. Table 3 lists the numerical changes in volume resistivity at different temperatures.

[0086] Table 3. Relationship between volume resistivity and temperature for different materials

[0087] As shown in Table 3, the volume resistivity of all materials decreased to varying degrees with increasing temperature. However, the volume resistivity of Examples 1, 2, and 3, which contained titanium carbide, remained relatively stable after heating. This is because in Example 3, the amount of titanium carbide added was small, insufficient to form a stable conductive network, and its effect on the volume resistivity was limited to the tunneling effect. Titanium carbide itself has a low Fermi level, and its doping into alumina as a conductive phase actually stabilizes its volume resistivity. Compared to Comparative Example 7, the volume resistivity rapidly decreased to the electrostatic conductivity range after heating to 200°C, indicating a significant improvement in performance.

[0088] Example 3, as the preferred embodiment of the present invention, has a strength of 1.13 × 10⁻⁶ at room temperature. 7 The volume resistivity is Ω·cm, and the decrease in volume resistivity at 500℃ is not significant, remaining at 1.68 × 10⁻⁶. 6 The Ω·cm value meets the national standard requirements for antistatic ceramic materials and is more in line with the current requirements of semiconductor manufacturers.

[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing antistatic alumina ceramic, characterized in that; The preparation method comprises the following steps: (1) Slurry ball milling: Alumina micro powder, silicon carbide micro powder, titanium carbide micro powder and yttrium oxide micro powder with weight parts of 69-77:15-25:1-5:0.5-3 respectively are mixed with water and then a dispersant is added. The mixture is ball milled to form slurry 1. The dispersant is a mixture including alumina dispersant and silicon carbide dispersant. The alumina dispersant is selected from ammonium salt type carboxylic acid copolymer and the silicon carbide dispersant is selected from polyacrylate-based composite dispersant. (2) Slurry grinding: Slurry 1 is mixed with binder and then ground and sieved to obtain slurry 2; (3) Spray drying: The slurry 2 is made into granulated powder; (4) The granulated powder is shaped into a green body, and the green body is degreased and sintered with argon gas to obtain an antistatic ceramic material. The degreasing process is as follows: the temperature is raised to 600-800℃ at a rate of 15-25℃ / h in nitrogen atmosphere and held for 1-2h. The sintering process is as follows: the temperature is raised to 1000-1100℃ at a rate of 50-100℃ / h in vacuum atmosphere, and then raised to 1900-2000℃ at a rate of 15-25℃ / h in argon atmosphere and held for 3-7h.

2. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, The alumina micro powder has a particle size of D10: 0.2-0.4µm, D50: 0.5-0.7µm, and D90: 2-4µm. The silicon carbide micro powder has a particle size of D10: 0.1-0.3µm, D50: 0.4-0.6µm, and D90: 0.9-1.1µm; it is used as a conductive filler in antistatic ceramics. The titanium carbide micro powder has a particle size of D10: 0.1-0.2µm, D50: 0.3-0.4µm, and D90: 0.5-0.6µm; it is used as a conductive filler in antistatic ceramics. The yttrium oxide micro powder has a particle size of D10: 0.3-0.5µm, D50: 0.8-1.0µm, and D90: 1.4-1.6µm; it is used as a sintering aid.

3. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, The amount of alumina dispersant used is 0.4%-0.8% of the weight of alumina micro powder; the amount of silicon carbide dispersant used is 0.4%-0.8% of the weight of silicon carbide micro powder.

4. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, The slurry 1 in step (1) has a solid content of 65%-70% and a viscosity of less than 100 Pa·s.

5. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, The adhesive used in step (2) is selected from polyvinyl alcohol-based composite adhesives, and the amount of adhesive used is 5-7% of the weight of the micro powder.

6. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, In step (3), a granulation tower is used for spray granulation with an inlet temperature of 160-200 ℃ and an outlet temperature of 60-80 ℃.

7. The method for preparing an antistatic alumina ceramic according to claim 1, characterized in that, In step (4), the granulated powder is formed by dry pressing or cold isostatic pressing to obtain a green body.

8. An application of an antistatic alumina ceramic, characterized in that: The antistatic alumina ceramic obtained by the preparation method of the antistatic alumina ceramic according to claim 1 is applied to semiconductor handling equipment.

Citation Information

Patent Citations

  • An antistatic alumina ceramic material and its preparation method

    CN113698182B

  • Ceramic material and electrostatic chuck apparatus

    CN108495829A

  • Magnetic head slider material, magnetic head slider, and method of manufacturing magnetic head slider material

    CN1724457A